Tabriz´’s Pol Bazaar as a Memory Place - Rostamzadehshabestari, Dilak; Say Özer, Yasemen (ICONARCH International Congress of Architecture and Planning, 2017)
Bazaar is a traditional public space in the Iranian cities, and has always been a great section of commercial activities in urban life. Bazaar is not only the commercial center of traditional cities in Iran but also the center of social, cultural, political and religious activities. The case study of this paper is the covered bazaar of Tabriz in the north west of Iran, with bridges which is connecting two separate parts of bazaar. In fact its hundreds of bridges built over the course of centuries, most of which are still in use today, and Tabriz probably has one of them. The Tabriz Historical Bazaar Complex is embodied with a largest integrated, covered brick structure and is the important economical-social system. Due to its strategically setting along the Silk Road, it has had strong interaction with other cultures in the world, from antiquity until the present. Tabriz bazaar has effected economical, cultural and political movements in Iran and has been a prototype for Persian urban planning. The main aim of this study is to explain the role of bazaar over bridges in the Tabriz historical bazaar and the difference of the Tabriz bazaar over bridge with other that is similar in other countries. The objective of this study is to explore the architectural features and strategic situation of Pol Bazaars which are the reminder from past as memory places.